Synthesis and Conformational Analysis of Fluorinated Pipecolic Acids - Singh, Sukhdev; Martinez, Claire-Marie; Calvet-Vitale, Sandrine; Prasad, Ashok K.; Prangé, Thierry; Dalko, Peter I.; Dhimane, Hamid (Synlett, 2012)
A short sequence to methyl cis- and trans-5-fluoro pipecolate is described via electrophilic fluorination of a pipecolate-based endocyclic enecarbamate by using Selectfluor® as a fluorinating agent. Methyl 5,5-difluoro pipecolate was also obtained by difluorodeoxygenation of the corresponding ketone, which was obtained in two steps from the same enecarbamate. The conformational profile of both methyl 5-fluoropipecolate isomers was investigated by NMR spectroscopy in solution and X-ray crystallography of the corresponding piperidinium picrates.
Keywords: pipecolic acid; enecarbamate; electrophilic addition; fluorine; stereoselectivity; fluoropipecolate; conformational analysis